POTENSI HABITAT JALAK BALI (Leucopsar rothschildi) DI TAMAN NASIONAL BALI BARAT - Fadlan Pramatana; Jarwadi Budi Hernowo; Lilik Budi Prasetyo (Wana Lestari, 2021)
Bali starling (Leucopsar rothschildi) is categorized as an endangered species based on IUCN, Appendix I based on CITES, and protected animals by the goverment of Indonesia. Bali Barat National Park (BBNP) has a breeding center for the recovery of species population in their natural habitat. The BBNP promoted soft release method for the introducing species in the wild habitat. This method consists of some treatments for supporting bali starling life and as consequently the distribution of species was concentrated in small area and the species can be monitored easily. This method has an effect the natural behaviour of bali starling is difficult to be formed and makes dependence on humans, and an effect on the shift of habitat choise by bali starling in BBNP. The problem is when the bali starling has been released to the wild. The number of individuals who have been released shows decrease fluctuation. This study was aimed to analyze potential of natural habitat. This study method using a vegetation analysis. The result found that the potential habitat with an importance value index is kemloko in the pole classification with a value 230.37% in the savanna ecosystem and talok with a value 86.27% in the monsoon forest ecosystem. The potential habitat in BBNP can still support the survival of bali straling.